(untitled) (Вісник: Міжнародні відносини, 2025)
Introduction. The Middle East has traditionally been a sphere of strategic interest for the United States, NATO, and the Euro-Atlantic community. The Syrian conflict became an arena for clashes between global and regional players, where the Russian Federation sought to strengthen its influence in opposition to the West. Aim. To analyze the relationship between Russia’s military intervention in Syria (2015) and its geopolitical confrontation with the Euro-Atlantic community, particularly in the context of Russia’s war against Ukraine, and to assess the impact of these processes on the regional order. Methods. A historical-comparative method was used to compare the stages of the Syrian conflict and the phases of the Russo-Ukrainian war, a case study method to analyze Russia’s intervention in Syria, as well as document analysis (official statements, agreements, position papers). Logical methods of analysis and synthesis were applied to identify cause-and-effect relationships between events in the Middle East and global changes. Results. It was found that Russia’s invasion of Ukraine in 2022 redirected significant resources to the Ukrainian front, leading to the weakening of its positions in Syria, the fall of the Bashar al-Assad regime in 2025, and the strengthening of Turkey’s influence in the region. The Euro-Atlantic community succeeded in uniting allies and partners from various regions into a single deterrence system, thereby strengthening its global position. Conclusions. Russia suffered a geopolitical defeat in Syria due to limited resources and strategic capabilities, which enhanced the role of the Euro-Atlantic community in shaping the new regional order in the Middle East.